Most cleaved anti-müllerian hormone binds its receptor in human follicular fluid but little is competent in serum - Pierre, Alice (2016)
Context: Anti-Müllerian hormone (AMH) is an important clinical marker for diagnosing and assessing the reproductive status and/or disorders in men and women. Most studies have not distinguished between levels of inactive AMH precursor and the cleaved noncovalent complex that binds the AMH type II receptor (AMHRII) and initiates signaling. Objective: The objective of the study was to measure the levels of AMH cleavage and bioactivity in human body fluids. Design, Setting, and Patients: AMH cleavage levels and bioactivity were measured in the serum of six boys and in the follicular fluid and serum of nine control women and 13 women with the polycystic ovary syndrome (PCOS). Main Outcome Measures: AMH cleavage levels were measured by capturing AMH with an anti- AMH antibody, followed by Western blotting. The bioactivity of cleaved AMH was assessed with an ELISA that measures the levels of AMH capable of binding AMHRII. Results: PCOS women have an elevated level of AMH cleavage in their follicular fluid (24% vs 8% in controlwomen),andmostofthecleavedAMHcanbindAMHRII.Higherlevels of cleavage areobserved in female (60%) and male (79%) serum, but very little of the cleaved AMH can bind AMHRII. Conclusions: These results support an autocrine role for AMH in the pathophysiology of PCOS in the follicle. In addition,theyindicate thatAMHundergoesinteractions or structuralchangesaftercleavage that prevent receptor binding, meaning, unexpectedly, that the level of cleaved AMH in biological fluids does not always reflect the level of bioactive AMH.